Analogues of Whittker’s theorem for Laplace-Stieltjes integrals - Dobushovskyy, M.S.; Sheremeta, M.M. (Carpathian Mathematical Publications, 2016)
For the maximum of the integrand of Laplace-Stieltjes integral the lower estimates on sequence are found. Using the estimates we obtained analogues of Whittaker's theorem for entire functions given by lacunary power series.